Removal of lead, cadmium, and chromium ions from aqueous solutions using iron (III) oxide - Munusamy, Shiva Shanthini (2022)
Lead (Pb), cadmium (Cd), and chromium (Cr) have been classified as heavy metals that have polluted the environment, mainly water sources. Therefore, the aim of this present study is to remove heavy metals, specifically Pb, Cd, and Cr ions from aqueous solutions using iron(III) oxide while, also contributing to the reduction of waste products that might ultimately cause environmental pollution. This study was designed to adopt adsorption technique to remove Pb, Cd, and Cr ions from the aqueous solutions with the help of low-cost adsorbent, iron(III) oxide, Fe2O3. The concentrations of Pb, Cd, and Cr ions in the aqueous solutions were then detected by Flame Atomic Absorption Spectroscopy (FAAS) instrument. Various parameters such as calcination temperatures of adsorbents, adsorbent dosages, and contact time were used to carry out the removal process of Pb ions. The effects of adsorption on different types of heavy metals, Cd and Cr as well as repeatability of adsorbents were also studied in this research. The FTIR findings revealed that certain heavy metals were more likely to bind to these adsorbents due to the presence of crucial functional groups such as hydroxyl (-OH) and carbonyl (C=O). From this study, the optimum removal conditions were calcination temperature of adsorbents of 400ºC, 0.2 g dose of adsorbent, and 60 minutes of contact time. The results showed that Fe2O3 adsorbents removed 0.912 mg/L, 0.540 mg/L, and 0.489 mg/L of Pb, Cd, and Cr ions from the aqueous solutions, suggesting that it was more efficient towards the removal of Pb ions. Repeatability study demonstrated that Fe2O3 adsorbent can be reused for three consecutive periods and thus, has a great potential for eliminating heavy metals from aqueous solutions. Hence, this study showed that the adsorption technique using Fe2O3 adsorbents was capable of removing Pb, Cd, and Cr ions from aqueous solutions. The reduction of these heavy metals' concentration by adsorbents can also assist to preserve good water quality that does not exceed the permissible limit by WHO.